Glycemic profile variability as an independent predictor of diabetic retinopathy in patients with type 2 diabetes: a prospective cohort study - Dehghani Firouzabadi, Fatemeh; Poopak, Amirhossein; Samimi, Sahar; Deravi, Niloofar; Nakhaei, Pooria; Sheikhy, Ali; Moosaie, Fatemeh; Rabizadeh, Soghra; Meysamie, Alipasha; Nakhjavani, Manouchehr; Esteghamati, Alireza (Frontiers in Endocrinology, 2024)
Background: Glycemic variability is a novel predictor for diabetic complications. Different studies have demonstrated contradictory results for the association between HbA1c variability and diabetic retinopathy. We aimed to assess the relationship between visit-to-visit variability in glycemic profile (HbA1c, 2hPP, FBS) and diabetic retinopathy.Methods: Patients with type 2 diabetes, were monitored for the development of retinopathy for 10 years. The association between the incidence of retinopathy and glycemic variability were assessed via cox regression analysis and coefficient of variation for glycemic indices were compared using independent sample t-test.Results: Patients with diabetic retinopathy had significantly higher glycemic profile variability.The incidence of retinopathy was positively correlated with cv-FBS10% (10 percent of coefficient of variances), cv-FBS20%, cv-2hpp10%, and cv-HbA1c5%. Our analysis revealed that higher variability of FBS increased the incidence and progression of retinopathy (HR: 12.29, pvalue: 0.003).Our findings demonstrated glycemic profile variability as an independent risk factor for diabetic retinopathy in patients with type 2 diabetes and support glycemic profile variability measurement in addition to common glycemic parameters to improve risk stratification in patients with type 2 diabetes. Further investigation is required to demonstrate the long-term effects of alleviating glycemic variability, on the prognosis of patients with type 2 diabetes.